Communication Ethic on Internet - Wandi Wandi (State Islamic Institute of Bone, Indonesia, 2021)
The advance of communication and information technology nowadays have contributed to a major impact on social life in the global world, one of them is the activity of communicating on the internet. The tendency and habit of communicating using the internet sometimes makes netizens forget the ethics in communicating and speak as they want, making rude comments, verbal abuse, bullying, blaspheming, and even offending the SARA (Ethnicity, Religion, Race, and Intergroup). From this phenomenon, this study aims to focus at the communication ethics the internet. This study employed a Library Research which is descriptively explained. The results of the study report that good ethics in communicating on the internet is very vital to maintain human relationships and survival among other humans. Therefore, there are some ethics in communicating on internet that we need to understand, such as considering about the good and bad impacts before sending messages on the internet, Using polite language, Having mutual respect in communicating on internet. Therefore, when communicating on internet, it must maintain good ethics and be wiser in using the internet so as to create harmony and happiness in social, national, and state life.